Estrategias didácticas para la escritura de textos narrativos en estudiantes de Educación Básica Superior - González Calva, María Cristina (2024)
Currently, education has undergone significant changes that require the adoption of new pedagogical approaches based on innovation and creativity. In this context, the present study aims to analyze the teaching strategies used by the Language and Literature teacher for narrative text writing, with students in the eighth and tenth years of Basic General Education, at the Unidad Educativa “La Dolorosa” in the Chaguarpamba canton, located in the Loja province. A qualitative methodology with a descriptive approach and a field research component was applied for its development. Information was collected through classroom observation, an interview with the main subject teacher, and the implementation of a formative assessment directed at the students. The results revealed a lack of effective strategies on the part of the teacher when delivering lessons related to narrative text composition. Consequently, it is concluded that the teacher lacks knowledge of what didactic strategies are, and therefore could not apply them in the eighth or tenth grade classes. This deficiency in adequate strategies hindered the generation of genuine interest among the students towards the subject and the topic discussed. In this context, it is crucial for educators to possess theoretical knowledge, as well as to be capable of implementing effective didactic strategies in their teaching practice that motivate and engage students in their learning process.